Energy resources, technologies and the environment - Ngo, Christian (London, United Kingdom The Institution of Engineering and Technology, 2010)
This book is aimed at students and professionals as well as anyone interested in having a global vision and perspective on energy.
Basic concepts -- Fossil fuels -- Renewable energies -- Nuclear energy -- Utilisation and storage -- Energy and the environment -- Future prospects.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Power resources; Electronic books